"ydx+(1\u22123y)xy=3ydy"
A first order linear differential equation in the form of "y'(x)+p(x)y=q(x)"
"y+(1-3y)xy=3y\\frac{dy}{dx}"
Substitute "\\frac{dy}{dx}=y'"
"y+(1-3y)xy=3yy'"
Rewrite,
"y'+xy=\\frac{1}{3}+\\frac{x}{3}"
Integration Factor : "IF = e^{\\frac{x^2}{2}}"
Differential Equation: "(IF\\times y)'= IF\\times q(x)"
"(e^{\\frac{x^2}{2}} \\times y)'= e^{\\frac{x^2}{2}} \\times \\frac{1}{3} +e^{\\frac{x^2}{2}} \\times \\frac{x}{3}"
"y = \\frac{\\sqrt 2 \\sqrt \\pi erfi \\frac{x}{\\sqrt 2}}{6e^{\\frac{x^2}{2}}}+\\frac{1}{3}+\\frac {c_1}{e^{\\frac{x^2}{2}}}"
Comments
Leave a comment